Unemployment, Labor Market Reform, and Monetary Union - Calmfors, Lars (Journal of Labor Economics, 2001)
Monetary union, such as the Economic and Monetary Union in Europe (EMU), may affect incentives for labor market reform, and thus equilibrium unemployment, through several mechanisms. If an inflation bias exists, there is usually a stronger incentive to reduce equilibrium unemployment through national reform outside rather than inside the EMU. Absent such a bias, EMU membership could lead to more reform. One reason is that reform may increase wage flexibility, which can substitute for monetary policy in the EMU. Another reason could be a precautionary motive for low equilibrium unemployment to reduce the utility cost of increased macroeconomic variability in the EMU.